Proposta de um conjunto de indicadores para medir o desempenho de um sistema de gestão da qualidade - Collette, Paulo Heitor (2019)
The Quality Management System (QMS), when efficient, is an important mean for controlling and help to achieve the company goals. To make the QMS efficient, there must be a way to measure, correct and improve the QMS. That can be done by using a set of performance indicators. The use of these indicators can help the correct direction of managers in the decision-making process. There are several studies and discussions about performance indicators with the objective of measuring the quality of products and processes. However, the use of performance indicators to measure the performance of quality management systems is a subject with few literature researches. By using such indicators, QMS can provide the necessary support for the organization processes to achieve planned quality, as it would be identifying and correcting problems by monitoring and improving their own performance. Thus, the purpose of this dissertation is the proposition of a set of performance indicators to measure performance and give the necessary support to the management of the organization QMS. Thus, the input criteria used were the quality management constructs, considered as variables used to measure quality performance. For the development of this research, a unique case study, with exploratory nature due to lack of research about the subject, was conducted in a multinational organization of the chemical sector. Interviews were conducted based on a checklist of support for data collection. The result of this study was the identification of 45 performance indicators divided into 11 groups organized based on the constructs, with the objective of measuring the performance of the QMS related to factors such as rate of utilization and expenses with the team, capacity level, development and motivation team, effectiveness of implemented action plans, discipline and compliance with defined activity deadlines, projects and audits, achievement of the goals agreed with the organization senior management, as well as the commitment level of QMS senior management regarding the team's own issues.